Representation of Women in Jo March's Character in the Novel Little Women: A Feminist Study - Rahmawati, Nurul; Anjany, Shagita Maulady (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2025)
Louisa May Alcott's Little Women is an American novel that describes the lives of women in the 19th century, when many social inequalities between men and women existed. Starting from these problems, the purpose of this research is to analyze the feminist values represented by the character Jo March. It examines the forms of social injustice and discrimination against women depicted in the novel as a reflection of women's real-world issues. It also explores and unveils the forms of resistance by the female characters. The primary data source is the novel Little Women by Louisa May Alcott, which is analyzed using Beauvoir's existentialist feminism approach and qualitative descriptive method. The results of the research show the existence of gender injustice, which limits women’s space through gender stereotypes, subordination of women, and objectification of women. The forms of resistance that demonstrate women's existence include fighting subordination, working to achieve financial independence, and becoming influential figures in society.